Laparoscopic liver resection for metastatic melanoma: a tale of caution and reason for optimism - Wilson, Gregory C.; Geller, David A. (Laparoscopic Surgery, 2018)
Reports of laparoscopic liver resection (LLR) date back to the early 1990’s (1,2). These reports were predominantly confined to retrospective case series from single institutions with a low number of overall patients. As acceptance of these technique grew and utilization expanded, an international consensus meeting was held in 2008 was held in Louisville, KY to review the safety of feasibility of this technique (3). Recommendations from this meeting established baseline terminology and efficacy of LLR.